Effects of Cash, Receivables, and Inventory Turns on the Profitability of Pharmaceutical Companies - Yulia Ayu Hanifah; Darno Darno (Neraca : Jurnal Akuntansi Terapan, 2020)
Competition in the business world makes each company increasingly able to improve its performance in order to achieve the company's goals to get the maximum profit so that the company is able to develop and compete with other companies. In this era of globalization, the emergence of new competitors in various industrial sectors of the company can make competition in business from the last few years very tight. So that requires each company to implement a management system in accordance with procedures in order to develop and run their businesses effectively. Theories that will be explained in this research are about Return on assets and Return On equity, and Net profit margin and also Company Value. This study used a non-experimental research type. Non-experimental research is a part of research in which observations can be carried out on a number of variables contained in the research subject reviewed according to the actual conditions without manipulation of data processed by the researcher. Because in this study the actual data used from the financial statements of pharmaceutical companies contained on the Stock Exchange regarding receivables turnover, as well as cash turnover as well as inventory turnover on profitability (Y). Receivables turnover, cash turnover and inventory turnover on a continuous and positive and significant effect on the profitability of pharmaceutical companies, especially those on the Indonesia Stock Exchange in 2014-2017. The results obtained after testing the hypothesis using the F-test and obtained a significant value <0.05. Where these results indicate there is a significant influence, so the hypothesis is very acceptable and proven true.